2021
DOI: 10.21603/2308-4057-2021-2-302-309
|View full text |Cite
|
Sign up to set email alerts
|

Macro- and microelements in some species of marine life from the Sea of Okhotsk

Abstract: Introduction. Residents of northern regions have a diet low in essential macro- and microelements. The Sea of Okhotsk is an enormous source of fish and non-fish products. We aimed to determine mineral contents in marine fish, shellfish, and algae in order to assess if they could satisfy the daily requirement for these elements through fish and non-fish consumption. Study objects and methods. Our study objects were saffron cod (Eleginus gracilis L.), blue-headed halibut (Reinhardtius hippoglossoides L.), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…The active components of algae can remove harmful elements from the human body and also have ulcer- and wound-healing properties. Microalgae extracts can increase hemoglobin concentration, reduce the level of sugar in the blood, and exhibit analgesic, bronchodilatory, and hypotensive activities [ 17 ]. As a result, more and more attention is being paid to applying algae in the pharmaceutical, cosmetic, and food industries [ 16 ].…”
Section: Introduction—characteristics Of Algaementioning
confidence: 99%
“…The active components of algae can remove harmful elements from the human body and also have ulcer- and wound-healing properties. Microalgae extracts can increase hemoglobin concentration, reduce the level of sugar in the blood, and exhibit analgesic, bronchodilatory, and hypotensive activities [ 17 ]. As a result, more and more attention is being paid to applying algae in the pharmaceutical, cosmetic, and food industries [ 16 ].…”
Section: Introduction—characteristics Of Algaementioning
confidence: 99%
“…At the same time, the biomass of macroalgae has significant resource potential [3,4]. There are some articles on macroalgae processing with the production of bioethanol [5], biogas [6,7], biofuels [2,8,9] nutrients [10], and biologically active substances [11].…”
Section: Introductionmentioning
confidence: 99%
“…Active research has identified a wide range of bioactive compounds in microalgae. It demonstrated that microalgae can be used to produce protein, polyunsaturated fatty acids, vitamins, minerals, and carbohydrates [ 5 , 6 ]. Through antioxidant properties, anti-inflammatory, antimicrobial, and antiviral effects, these compounds may play an important role in cattle, poultry, shellfish, and fish feed, as well as human functional foods, contributing to the prevention of stomach ulcers, constipation, anemia, diabetes, and hypertension [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%